2017
DOI: 10.1002/bit.26363
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional engineering of the glyceraldehyde‐3‐phosphate dehydrogenase promoter for improved heterologous protein production in Pichia pastoris

Abstract: The constitutive glyceraldehyde-3-phosphate dehydrogenase promoter (P ), which is one of the benchmark promoters of Pichia pastoris, was analyzed in terms of putative transcription factor binding sites. We constructed a synthetic library with distinct regulatory properties through deletion and duplication of these putative transcription factor binding sites and selected transcription factor (TF) genes were overexpressed or deleted to understand their roles on heterologous protein production. Using enhanced gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 42 publications
0
47
0
2
Order By: Relevance
“…The base plasmid pPICZα-A::eGFP (Ata et al, 2017) was used in the construction of recombinant eGFP expression cassettes. The list of primers designed and used is given in Method S1.…”
Section: Strains Primers and Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations
“…The base plasmid pPICZα-A::eGFP (Ata et al, 2017) was used in the construction of recombinant eGFP expression cassettes. The list of primers designed and used is given in Method S1.…”
Section: Strains Primers and Plasmidsmentioning
confidence: 99%
“…Efficient and tuneable promoter selection is crucial for recombinant protein production as it precedes and starts with the transcription of the target gene which is the first step of protein synthesis, wherein P. pastoris, these are often derived from carbon source utilization pathways. The results of the latter two work revealed that the strains constructed with P GAP variants and the NONPs produced considerable amounts of ethanol as a byproduct and, synthesized and secreted more recombinant protein than the strain constructed with P GAP (Ata et al, 2017;Massahi & Çalık, 2018). P GAPbased fermentation processes in glucose-based defined media are advantageous for the production of biopharmaceuticals compared to P AOX1 -based fermentations using methanol, since nontoxic carbon source containing media also may simplify downstream purification and regulatory documentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These HFBB design parameters change depending on the promoter architecture ( i.e . by promoter variants and transcriptional engineering) and with novel promoter systems due to changes occurring in the flow of C molecules through the pathways. A related article concerning the latter is under preparation by our research group.…”
Section: Discussionmentioning
confidence: 99%